Cost-effectiveness of Population-Based BRCA1, BRCA2, RAD51C, RAD51D, BRIP1, PALB2 Mutation Testing in Unselected General Population Women. (18th January 2018) - Manchanda, Ranjit; Patel, Shreeya; Gordeev, Vladimir S; Antoniou, Antonis C; Smith, Shantel; Lee, Andrew; Hopper, John L; MacInnis, Robert J; Turnbull, Clare; Ramus, Susan J; Gayther, Simon A; Pharoah, Paul D P; et al.
Abstract: Background: The cost-effectiveness of population-based panel testing for high- and moderate-penetrance ovarian cancer (OC)/breast cancer (BC) gene mutations is unknown. We evaluate the cost-effectiveness of population-based BRCA1/BRCA2/RAD51C/RAD51D/BRIP1/PALB2 mutation testing compared with clinical criteria/family history (FH) testing in unselected general population women. Methods: A decision-analytic model comparing lifetime costs and effects of criteria/FH-based BRCA1/BRCA2 testing is compared with BRCA1/BRCA2/RAD51C/RAD51D/BRIP1/PALB2 testing in those fulfilling clinical criteria/strong FH of cancer (≥10% BRCA1/BRCA2 probability) and all women age 30 years or older. Analyses are presented for UK and US populations. Identified carriers undergo risk-reducing salpingo-oophorectomy. BRCA1/BRCA2/PALB2 carriers can opt for magnetic resonance imaging/mammography, chemoprevention, or risk-reducing mastectomy. One-way and probabilistic sensitivity analysis (PSA) enabled model uncertainty evaluation. Outcomes include OC, BC, and additional heart disease deaths. Quality-adjusted life-years (QALYs), OC incidence, BC incidence, and incremental cost-effectiveness ratio (ICER) were calculated. The time horizon is lifetime and perspective is payer. Results: Compared with clinical criteria/FH-based BRCA1/BRCA2 testing, clinical criteria/FH-based BRCA1/BRCA2/RAD51C/RAD51D/BRIP1/PALB2 testing is cost-effective (ICER = £7629.65/QALY or 49 282.19/QALY; 0.04 days' life-expectancy gained). Population-based testing for BRCA1/BRCA2/RAD51C/RAD51D/BRIP1/PALB2 mutations is the most cost-effective strategy compared with current policy: ICER = £21 599.96/QALY or 54 769.78/QALY (9.34 or 7.57 days' life-expectancy gained). At £30 000/QALY and 100 000/QALY willingness-to-pay thresholds, population-based BRCA1/BRCA2/RAD51C/RAD51D/BRIP1/PALB2 panel testing is the preferred strategy in 83.7% and 92.7% of PSA simulations; criteria/FH-based panel testing is preferred in 16.2% and 5.8% of simulations, respectively. Population-based BRCA1/BRCA2/RAD51C/RAD51D/BRIP1/PALB2 testing can prevent 1.86%/1.91% of BC and 3.2%/4.88% of OC in UK/US women: 657/655 OC cases and 2420/2386 BC cases prevented per million. Conclusions: Population-based BRCA1/BRCA2/RAD51C/RAD51D/BRIP1/PALB2 testing is more cost-effective than any clinical criteria/FH-based strategy. Clinical criteria/FH-based BRCA1/BRCA2/RAD51C/RAD51D/BRIP1/PALB2 testing is more cost-effective than BRCA1/BRCA2 testing alone.